Prevalence of Workplace Bullying and Its Associated Factors at a Multi-Regional Saudi Arabian Hospital: A Cross-Sectional Study - Al-Surimi K; Al Omar M; Alahmary K; Salam M (Dove Medical Press, 2020)
Khaled Al-Surimi,1,2 Munirah Al Omar,1,2 Khalid Alahmary,1,2 Mahmoud Salam1– 3 1Department of Health System Management, College of Public Health and Health Informatics, King Saud bin Abdulaziz University for Health Sciences, Riyadh, Saudi Arabia; 2King Abdullah International Medical Research Center, Riyadh, Saudi Arabia; 3Hariri School of Nursing, American University of Beirut, Beirut, LebanonCorrespondence: Mahmoud SalamKing Saud bin Abdulaziz University for Health Sciences, King Abdullah International Medical Research Center, Riyadh 22490, Saudi ArabiaTel +96170054397Email mahmoudsalam@hotmail.comBackground: Workplace bullying (WPB) refers to any form of repeated and unreasonable verbal, physical or sexual harassment that an employee endures by a person or a group. In healthcare settings, practitioners are occasionally victims of WPB incidents. The aim of this study was to survey victims of WPB and determine factors associated with being a victim of WPB at a multiregional health care facility in Saudi Arabia.Methods: This cross-sectional study was conducted in 2018, by distributing a self-administered questionnaire via a private electronic mail to all fulltime healthcare practitioners within a multi-regional hospital in Saudi Arabia. Healthcare practitioners included physicians, nurses, allied healthcare professionals and pharmacists who reported being exposed to WPB in the past year. Study outcomes were the prevalence rate ratio of WPB and its associated factors, such as victim, perpetrator and incident characteristics.Results: WPB has been reported by 684 participants. Perpetrators were mainly patients (36.1%), their families/relatives (29.5%), and hospital staff (27.2%) or managers/supervisors (7.2%). The type of WPB incident was mostly verbal abuse (98.1%) followed by physical harassment (11.8%) and sexual connotations (5.8%). WPB was 30% more prevalent among younger nurses and 24% less prevalent among higher educated nurses compared to their counter groups, P< 0.001 each. Among technicians and administrative employees, WPB was 54% more prevalent among females, 36% more prevalent among the younger group, and 25% more prevalent among expatriate workers compared to their counter groups P< 0.014, P< 0.001 and P=0.017, respectively. WPB was 20% less prevalent among higher educated allied health professionals, P=0.002. Among physicians, WPB was 33% more prevalent among females, P=0.041 and was 47% more prevalent among higher educated physicians compared to their counter groups, P=0.018.Conclusion: WPB might occur any time, anywhere and by any person within health care facilities. The prevalence of WPB varies within health occupational groups. Gender, age, educational level, and nationality were significantly associated factors with WPB.Keywords: nurse, physician, pharmacist, bullying, verbal, physical, sexual